The Acquisition of Prepositional Meanings in L2 Spanish - Lam, Yvonne (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2018)
This study examines how adult second language learners acquire the different meanings of the Spanish preposition a. Cognitive linguistic models predict that spatial meanings are acquired first, as they are conceptually basic and are the source from which other meanings derive via natural cognitive mechanisms such as metaphor and image-schema transformation (Tyler & Evans, 2003). However, there has been little empirical evidence to support this hypothesis. Results from an oral story-telling task conducted with beginner (N = 10), intermediate (N = 10), and advanced (N = 4) learners suggest that the acquisition of prepositional meanings is not driven solely by cognitive mechanisms, but rather that other non-conceptual factors, such as collocational patterns, cross-linguistic transfer, frequency, and saliency, also play a prominent role. These findings imply that learners approach the multiple varied meanings of a preposition by relying on several different mechanisms simultaneously.